Use of cocoa ethanolic extract for treatment of Staphylococcal infection in rabbit-skin model - Ariza Budi Tunjung-Sari; Teguh Wahyudi; Diana Chusna Mufida; Mekania Tamarizki; Desyana Perwitahati; Ihda Kartika Syamsuddin; Misnawi Jati (Indonesian Coffee and Cocoa Research Institute, 2016)
In septic condition, the skin normal flora Staphylococcal spp. may trigger local and sistemic skin infection. In this study antibacterial activity of cocoa ethanolic extract (CEE) against Staphylococcus aureus and Staphylococcus epidermidis infections was observed in vitro and in vivo. Ethanolic extract from unfermented cocoa beans was prepared as solution in the in vitro testing, while for in vivo testing the extract was prepared as cream. Agar well diffusion assay showed that CEE ranging from 7.8 mg/mL to 1000 mg/mL demonstrated inhibitory activity against growth of either S. aureus and S. epidermidis. Inhibitory activity of CEE was in concentration dependent manner, and was less potential than either cephalexin 4 x 10 -3 mg/mL or cefotaxime 8 x 10 -3 mg/mL. Linear regression of CEE concentration plotted against inhibition zone values ha dpredicted the minimum inhibitory concentrations (MIC) of CEE towards S. aureus and S. epidermidis were at 341.9 mg/mL and 359.7 mg/mL, respectively. Topical application of cream containing CEE at several concentrations (2%, 4%, and 8%) demonstrated healing properties towards incision wound infected with S. aureus and S. epidermidis cultures in rabbit-skin model. CEE cream promoted wound contraction and higher recovery rate than of base cream (negative control) but lower than mupirocin 2% cream. In S. aureus and S. epidermidis infected wound models, CEE cream 8% improved wound recovery to 72.7% and 86.1% from original rates of 23.5% and 34.7% (base cream application). Catechin and procyanidis are suggested playing roles in alleviation of wound inflammation and stimulation of extracellular matrix accumulation, thus accelerate the wound healing process. This study proposes utilization of cocoa bean as source of active ingredient for skin care products.